Analysis of Factors Influencing Students' Interest in Stock and Cryptocurrency Investments: A Study on Indonesian University Students' Behavioral Intentions Using the Theory of Planned Behavior - Callista, Vania; Handoko , Liza (Manunggal Halim Jaya, 2025)
Investment interest among Indonesian university students remains low, particularly in stocks and cryptocurrency. Data shows that most capital market investors in Indonesia have only completed high school, while undergraduate students have lower investment participation. Understanding the factors influencing students' investment interest is crucial to fostering financial literacy and economic growth. This study examines the factors affecting students' interest in investing in stocks and cryptocurrency using the Theory of Planned Behavior (TPB). A quantitative approach was employed, with data collected from 200 university students in Indonesia who have previously invested in stocks (n=100) or cryptocurrency (n=100). The study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. Findings reveal that Perceived Behavioral Control (PBC) plays a significant mediating role in the relationship between Attitude Towards Behavior (ATB) and Intention to Invest (ITI) in the stock market. Meanwhile, Subjective Norms (SN) exert a more substantial influence on cryptocurrency investment, directly and indirectly. This indicates that financial literacy and confidence in decision-making are key drivers for stock investments, whereas social influence plays a dominant role in cryptocurrency investments. The results highlight the need for educational institutions to integrate financial literacy programs and provide simulated investment experiences to enhance students' investment confidence and motivation.